2008
DOI: 10.1163/156856208786052353
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen and von Willebrand factor mediated platelet adhesion to polystyrene under flow conditions

Abstract: The roles of adsorbed fibrinogen (Fg) and von Willebrand factor (VWF) in mediating platelet adhesion to synthetic surfaces under flow were investigated using polystyrene (PS) as a model hydrophobic surface. We measured platelet adhesion to PS pre-adsorbed with Fg, VWF, normal plasma, afibrinogenemic plasma, VWF-deficient plasma and deficient plasmas with various concentrations of added Fg or VWF. Platelets in a red blood cell suspension were passed through a flow chamber at either low (50 or 100 s(-1)) or high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 74 publications
(65 reference statements)
1
14
0
Order By: Relevance
“…This verifies that the increase seen in the work by the Bartlett group is likely influenced to the release of NO from the surface and not the surface properties as previously thought . Fibrinogen is an active protein in the coagulation cascade, the increase of fibrinogen adsorption to a surface is currently viewed as leading to an increase in clot formation . We find that there is an increase in the amount of fibrinogen adsorbed to the NO‐releasing surface when compared to that of the control.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This verifies that the increase seen in the work by the Bartlett group is likely influenced to the release of NO from the surface and not the surface properties as previously thought . Fibrinogen is an active protein in the coagulation cascade, the increase of fibrinogen adsorption to a surface is currently viewed as leading to an increase in clot formation . We find that there is an increase in the amount of fibrinogen adsorbed to the NO‐releasing surface when compared to that of the control.…”
Section: Discussionsupporting
confidence: 85%
“…22 Fibrinogen is an active protein in the coagulation cascade, the increase of fibrinogen adsorption to a surface is currently viewed as leading to an increase in clot formation. 47,48 We find that there is an increase in the amount of fibrinogen adsorbed to the NO-releasing surface when compared to that of the control. This is in contrast to a study done by Charville et al 18 where they see that the adsorption of fibrinogen to control and NO-releasing xerogels remains constant.…”
Section: Discussionmentioning
confidence: 71%
“…In a shear flow system of platelet rich plasma, Zhang et al [60] showed that platelets adhere to biomaterials through a mechanism mediated by both fibrinogen and von Willebrand’s factor. The presence of plasma proteins like von Willebrand’s factor augment the ability of activated platelets to adhere to artificial surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…In subsequent studies, we further investigated the role of Fg and vWf on platelet adhesion from washed platelet‐red cell suspensions under flow conditions . All of these studies showed a major role for vWf in promoting platelet adhesion under high flow conditions.…”
Section: Selective Depletion Studies Establish a Major Role For Fg Inmentioning
confidence: 96%
“…In subsequent studies, we further investigated the role of Fg and vWf on platelet adhesion from washed platelet-red cell suspensions under flow conditions. 8,4850 All of these studies showed a major role for vWf in promoting platelet adhesion under high flow conditions. Thus, for example, platelet adhesion to surfaces preadsorbed with normal plasma is greatly increased when the shear rate is increased from 50 to 500 sec −1 because of more rapid transport of the platelets to the surface at higher shear rate.…”
Section: Selective Depletion Studies Establish a Major Role For mentioning
confidence: 99%